Exploring Biases in Machine Learning Models for Neurodegenerative Diseases Diagnosis Through Gait and Voice Analysis - Chagas, Ana Luísa de Bastos; Bucci, Giordana de Farias F. B.; Félix, Juliana Paula; Salvini, Rogerio; Nascimento, Hugo; Soares, Fabrizzio (Anais Estendidos do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2025)
This work examines potential biases in machine learning models for diagnosing neurodegenerative diseases (NDDs) through gait and voice analysis. It investigates how common techniques, such as gait signal windowing and using multiple voice samples per individual indiscriminately, can lead to inflated performance estimates when samples from the same individual are treated independently. Using two public databases, it compares scenarios where augmented samples are treated independently versus grouped by individual. Results show that independent treatment leads to artificially higher performance metrics. The findings highlight the need for proper intra-individual variability handling to ensure reliable clinical decision support for NDD diagnosis.